2021
DOI: 10.1016/j.ces.2021.116666
|View full text |Cite
|
Sign up to set email alerts
|

Development of a kinetic model for low temperature Fischer-Tropsch synthesis

Abstract: Globally, there is a need to replace our dependence on fossil fuels as the main source of energy.This requires a shift towards renewable and sustainable alternatives. The well-established Fischer-Tropsch (FT) synthesis is a potential process route to produce liquid fuels and speciality chemicals and address this challenge. FT synthesis is a polymerisation reaction in which syngas, a mixture of CO and H 2 , is converted to hydrocarbon products ranging from methane to wax when low temperature conditions are used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 72 publications
(454 reference statements)
1
5
1
Order By: Relevance
“…Hence, it was predicted that the selectivity towards jet fuel (C 8 –C 16 ) at the RNC catalyst would be greater in comparison to the FTS products, in particular, liquid fuels. Besides, from a thermodynamic point of view, methane is the most probable product in FTS, which is according to the reports by Davies et al and Zaffran et al , 47,48 and the Δ G results that were extracted from MD computations confirm this. The MD simulation results illustrate that Δ G for methane formation, 0.29 and 0.26 kcal mol −1 in NC and RNC catalysts, respectively, have the lowest values and Ru boosts its formation.…”
Section: Resultssupporting
confidence: 74%
“…Hence, it was predicted that the selectivity towards jet fuel (C 8 –C 16 ) at the RNC catalyst would be greater in comparison to the FTS products, in particular, liquid fuels. Besides, from a thermodynamic point of view, methane is the most probable product in FTS, which is according to the reports by Davies et al and Zaffran et al , 47,48 and the Δ G results that were extracted from MD computations confirm this. The MD simulation results illustrate that Δ G for methane formation, 0.29 and 0.26 kcal mol −1 in NC and RNC catalysts, respectively, have the lowest values and Ru boosts its formation.…”
Section: Resultssupporting
confidence: 74%
“…This remark is important for proper understanding of the proposed living growth mechanism, as diffusion can control the chain length, as the effective-constants fall with the chain size. Particularly, Davies and Möller observed that the product distribution might be controlled by the chemical equilibrium, while the hydrocarbon yield was kinetically controlled. In this case, the reduction of the kinetic rate constants might indicate the occurrence of other parallel reactions besides chain growth.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, WGS and Boudouard reactions are less exothermic compared to the hydrogenation reactions. Based on the Gibbs free energy analysis, it can be speculated that higher temperatures favor the WGS and Boudouard reactions and the formation of short-chain products. , Davies et al . developed an equilibrium-constrained kinetic model to predict the hydrocarbon distribution (Figure a)–d).…”
Section: Steering the Structural Evolution: The Role Of Reactive Envi...mentioning
confidence: 99%
“…Based on the Gibbs free energy analysis, it can be speculated that higher temperatures favor the WGS and Boudouard reactions and the formation of short-chain products. 147,148 Davies et al 149 developed an equilibrium-constrained kinetic model to predict the hydrocarbon distribution (Figure 25a)−d). It was found that the product distribution was equilibrium-controlled, while the yield of hydrocarbon products was kinetically controlled.…”
Section: Conventional Thermal Catalysis Versus Nonconventional Catalysismentioning
confidence: 99%
See 1 more Smart Citation